The functions of the ideas of pure reason - Debernardi Cárcamo, Italo Angelo (Pensamiento. Revista de Investigación e Información Filosófica, 2019)
The purpose of this paper is to analyze the functions of the ideas of pure reason, focusing on this treatment of this subject in the Appendix that concludes the Transcendental Dialectic of the Critique of Pure Reason. In particular, it addresses the systematizing function of the ideas and the problem of their hypothetical or regulative use, as well as the link between both functions. It will present how the reason’s search for systematic unity makes possible the coherent use of the understanding, and how ideas, as focus imagarius, guide the understanding and widen the knowledge and the scope of the experience given from the outside of the possible empirical knowledge.